Analysis of Women's Involvement in Marine Mining: Motivation, Challenges, and Perceptions of the Local Community of Belo Laut Village Mentok District West Bangka Regency - Rangga Juanda; Naswa Okta; Suci Espiana; Aditya Putra; Ririn Septia (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2025)
This study analyzes the involvement of women in the marine mining sector in Belo Laut Village, Mentok District, West Bangka Regency. Mining activities are indetik with masculine activities that must have physical strength, but women in Belo Laut Village play an important role in going through mining activities commonly called